Becoming a Teenager after Early Surgical Ventricular Septal Defect (VSD) Repair: Longitudinal Biopsychological Data on Mental Health and Maternal Involvement - Lang, Laura; Gerlach, Jennifer; Plank, Anne-Christine; Purbojo, Ariawan; Cesnjevar, Robert; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Journal of Clinical Medicine, 2022)
Beside somatic strains of congenital heart diseases (CHD), affected children often show developmental impairments in the long term. Ventricular septal defect (VSD) is the most common congenital heart defect and early surgical repair is associated with positive somatic outcomes. However, psychological adjustment is of lifelong relevance. We investigated 24 children with a surgically-corrected isolated VSD and their mothers from primary school (6–9 years) to adolescence (10–14 years) and compared them to controls. Both times, mothers reported child internalizing/externalizing problems, mothers and children rated child quality of life, and children performed neurodevelopmental tests. Adolescents also rated internalizing/externalizing problems themselves, and their hair cortisol levels were analyzed. Maternal anxiety and proactive parenting behavior were considered as moderators. Results revealed no group differences in child neurodevelopment (language, cognition), externalizing problems, and cortisol levels at any time. In reports from mothers, internalizing problems (depression, anxiety) were elevated in children with a VSD at both times—when mothers reported anxiety symptoms themselves. In adolescent reports, VSD patients’ quality of life was increased and internalizing problems were decreased—proactive parenting behavior went along with decreased symptoms in VSD-affected adolescents and with increased symptoms in controls. The findings pronounce the crucial role of parenting behavior and the influence of maternal anxieties on child mental health after surgical VSD repair and might highlight the need for parent-centered interventions.
CRIS-Team Scopus Importer:2022-12-23
Keywords: adolescence; child development; congenital heart disease; cortisol; longitudinal study; mental health; psychological adjustment; quality of life; stress; ventricular septal defect